APPLICATION OF THE RULES OF COMMANDMENTS AND PROHIBITIONS IN TAFSIR AL-MISHBAH - Abur Hamdi Usman; Mazlan Ibrahim; Mohd Farid Ravi Abdullah (Taqaddumi: Journal of Quran and Hadith Studies, 2021)
Shihab, in full M. Quraish Shihab (b. 1944) is a prominent exegete who became one of the leading intellectual figures of 20th-century Indonesia. As a scholar, Shihab is best remembered for his 30-chapter exegesis entitled Tafsir Al-Mishbah. In the Commentary, Shihab had applied several rules that had driven him towards exegeting the verses. This kind of rule is also adopted by the other exegetes to ensure their exegeses are in line with the Islamic law. Therefore, this paper seeks to analyze the rules of interpretation applied by Shihab which focuses on the discussions of commandments (al-amr) and prohibitions (al-nahy). To get a proper understanding and to ensure the rules that Shihab had employed can be analysed perfectly, We adopted the document analysis method by making language scriptures and venerated exegeses as the main sources of references. The study found that Shihab had applied six rules related to al-amr and al-nahy in his Tafsir Al-Mishbah, and the rules have been affirmed by grand exegetes.